Change in COVID-19 Pandemic: Investigating Early Childhood Education Teachers’ Technological Pedagogical Content Knowledge (TPACK) Competencies - Ria Novianti; Eddy Noviana; Wilson Wilson; Meyke Garzia; Tri Umari (STAI Hubbulwathan Duri, 2023)
This study delved into the realm of early childhood education, specifically focusing on the Technological Pedagogical Content Knowledge (TPACK) of teachers in Riau Province, Indonesia. Quantitative data were gathered from a sample of 124 early childhood educators catering to children aged 3 to 5 in school-based settings. The research utilized an instrument adapted from Kabakci Yurdakul's TPACK-Deep survey, tailored to suit the unique educational landscape of early childhood education in Indonesia. Data analysis primarily involved descriptive techniques. The findings underscored the imperative for teachers to enhance their TPACK competencies to effectively tackle emerging challenges and elevate the quality of education, aligning with the evolving demands of children's educational needs. However, a notable gap emerged as many educators struggled to integrate technology into their teaching practices, often due to insufficient access to necessary technological resources. This highlights the pressing need for educators to continuously hone their expertise in technology, pedagogy, and content knowledge to optimize learning experiences for young learners.